2010
DOI: 10.1159/000319527
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Genetic Studies in a Hypospadic Horse (Equus caballus, 2n = 64)

Abstract: A 4-year-old male horse of Friesian breed with normal body conformation, development and libido, and showing an evident ventral penis deviation with hypospadias, underwent both cytogenetic and genetic investigation. Although the karyotype showed normal male arrangement (2n = 64,XY), one telomere of horse (ECA) chromosome 1 was shorter than both the other one and those of a normal horse (control), as revealed by CBA- and RBA-banding, and by Ag-NOR and FISH-mapping techniques using telomere PNA probes. Genetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Some of the mutations appeared to be causative and some were only associated with the intersexual phenotype. The MAMLD1 sexlinked gene was studied in a hypospadic stallion and 1 missense substitution was identified (Leu108Ile), but it could not be clarified whether this mutation is causative [De Lorenzi et al, 2010]. In our study we identified several polymorphisms in both genes, which were spread in intersexual and normal dogs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Some of the mutations appeared to be causative and some were only associated with the intersexual phenotype. The MAMLD1 sexlinked gene was studied in a hypospadic stallion and 1 missense substitution was identified (Leu108Ile), but it could not be clarified whether this mutation is causative [De Lorenzi et al, 2010]. In our study we identified several polymorphisms in both genes, which were spread in intersexual and normal dogs.…”
Section: Discussionmentioning
confidence: 77%
“…There are several reports presenting this disorder in horse [De Lorenzi et al, 2010], cattle [Alam et al, 2005], pig [Finnigan et al, 2005] and sheep [Smith et al, 2006]. Unfortunately, until now no gene mutation has been identified which could be considered as a cause for a monogenic form of hypospadias nor a polymorphism predisposing to the development of a multigenic form of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A third case, also a Friesian, was reported to have hypospadias with ventrocaudal penis deviation and a depigmented area of skin in the perineum [De Lorenzi et al, 2010] and a normal karyotype of 64,XY. SRY sequencing did not produce any abnormalities.…”
Section: Hypospadias (64xy)mentioning
confidence: 97%
“…For example, a lack of association between the polymorphisms in the 3 genes considered in the present study and hypospadias has been described in 3 DSD cats [Nowacka-Woszuk et al, 2014]. An interesting case of a homozygous genotype for a missense substitution in the MAMLD1 gene was found in a hypospadic horse, but its association with the observed abnormality was not confirmed [De Lorenzi et al, 2010]. Polymorphism studies of candidate genes for human hypospadias or cryptorchidism have been extensively done [Docampo and Hadziselimovic, 2015;Khan et al, 2018].…”
Section: Resultsmentioning
confidence: 70%